Given:
a4 = 98
a5 = 99.2
a6 = 100.4
a7 = 101.6
a8 = 102.8
Use the arithmetic sequence formula below:
[tex]a_n=a_1+(n-1)d[/tex]Where,
an = nth term
a1 = first term
n = number of terms
d = common differnce
Let's solve for the common differnce.
d = a5 - a4 = 99.2 - 98 = 1.2
Use the 8th term a8, to find the first term:
[tex]\begin{gathered} 102.8=a_1+(8-1)1.2_{} \\ \\ 102.8=a_1+(7)1.2 \\ \\ 102.8=a_1+8.4 \\ \\ a_1=102.8-8.4\text{ = 94.4} \end{gathered}[/tex]Therefore, the first term a1 = 94.4
Thus, the equation for the nth term will be:
Input 94.4 for a1, 1.2 for d in the arithmetic formula above
[tex]\begin{gathered} a_n=94.4+(n-1)1.2 \\ \\ a_n=94.4+1.2n-1.2 \\ \\ \text{combine like terms:} \\ a_n=1.2n+94.4-1.2 \\ \\ a_n=1.2n+93.2 \end{gathered}[/tex]ANSWER:
[tex]a_n=1.2n+93.2[/tex]